2020
DOI: 10.1038/s41598-020-74190-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of foveal avascular zone with the metamorphopsia in epiretinal membrane

Abstract: This study was to investigate the relationship between the metamorphopsia and foveal avascular zone (FAZ) parameter in eyes with epiratinal membrane (ERM). We studied patients with an ERM visited retinal service unit at the Kagoshima University Hospital or Shirai Hospital. The best-corrected visual acuity (BCVA), and the degree of metamorphopsia by M -CHARTS™ were evaluated. The 3 × 3 mm optical coherence tomography angiography (OCTA) images of the superficial layer were obtained. Area (mm2), the circularity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
4
14
0
Order By: Relevance
“…Shiihara and colleagues assessed the shape of the FAZ in addition to the area of the FAZ in ERM eyes. 19 Interestingly, they reported that 68.5% of ERM eyes had a horizontally long-shaped FAZ, whereas 31.5% had a vertically long-shaped FAZ, supporting our current results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Shiihara and colleagues assessed the shape of the FAZ in addition to the area of the FAZ in ERM eyes. 19 Interestingly, they reported that 68.5% of ERM eyes had a horizontally long-shaped FAZ, whereas 31.5% had a vertically long-shaped FAZ, supporting our current results.…”
Section: Discussionsupporting
confidence: 90%
“… 8 More recently, the foveal avascular zone (FAZ), measured with OCT angiography, was reportedly correlated with metamorphopsia in ERM. 19 In the current study, the two-dimensional parameter, YCA, was associated with visual function. In the present study, the YCA was not compared with OCT parameters, such as INL thickness, retinal fold depth, and FAZ, but a significant merit of the current approach is that visual function can be predicted using the retinal artery angle, which can be easily obtained using only UWF imaging.…”
Section: Discussionmentioning
confidence: 62%
“…The presence of EIFL in eyes with ERM was associated with worse visual acuity, and the thickness of EIFL was negatively correlated with visual acuity [ 7 , 14 ]. More recent studies have shown that the EIFL grading scheme showed a good correlation not only with BCVA or CMT but also with other functional and anatomical parameters such as metamorphopsia and FAZ parameters [ 15 , 16 ], which was in agreement with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the final effect of the operation depends on changes of the foveal vasculature, which disperses the light before it reaches the photoreceptor cells [ 18 ]. Measurement of FAZ area in patients with ERM is paramount, because the degree of metamorphopsia is significantly correlated with the area of FAZ in these patients [ 19 ]. The morphology, structure, and area of FAZ are predictive factors for the requirement of retinal membrane surgery [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the final effect of the operation depends on changes of the foveal vasculature, which disperses the light before it reaches the photoreceptor cells [18]. Measurement of FAZ area in patients with ERM is paramount, because the degree of metamorphopsia is significantly correlated with the area of FAZ in these patients [19]. The morphology, structure, and area of FAZ are predictive factors forthe requirement of retinal membrane surgery [20].The present study confirmed the association between FAZ In the control group, there was a statistically significant Spearman correlation for the variables age and quality macula (r = −0.404); in the ERM group, this correlation is much smaller and insignificant (r = −0.04).…”
Section: Discussionmentioning
confidence: 99%